Complete genome sequences of three novel pseudomonas fluorescens SBW25 Bacteriophages, Noxifer, Phabio, and Skulduggery - Hendrickson HL (American Society for Microbiology)
Three novel bacteriophages, two of which are jumbophages, were isolated from compost in Auckland, New Zealand. Noxifer, Phabio, and Skulduggery are double-stranded DNA (dsDNA) phages with genome sizes of 278,136 bp (Noxifer), 309,157 bp (Phabio), and 62,978 bp (Skulduggery).
Keywords: 0601 Biochemistry and Cell Biology; 0604 Genetics; 0605 Microbiology